The Mycobacterium tuberculosis KatG gene : identification of a novel function and analysis of the regulation of expression - Mulder, Michelle Anne (Division of Medical Microbiology, 2017)
A clone containing the terminal third of the Mycobacterium tuberculosis katG gene was previously shown to confer resistance to ethyl methane sulfonate on DNA repair-deficient Escherichia coli cells. The first aim of this study, therefore, was to examine the role played by the M tuberculosis katG gene in DNA repair. The strategy used was overexpression of different regions of the gene in DNA repair-deficient mutants of E. coli, and examination of the sensitivities of the transformants to DNA damaging agents. Overexpression of the gene resulted in an increase in the survival of recA mutants exposed to ultraviolet (UV) light irradiation (254 run) and hydrogen peroxide, and uvr mutants exposed to mitomycin C. Both the 5' and 3' regions of the M tuberculosis KatG protein conferred the above effects, and this was independent of the catalase or peroxidase activity of the enzyme. The results suggest that the M tuberculosis katG gene may encode a novel function related to the repair of DNA damage, and this may have implications for the survival of M tuberculosis in the presence of DNA damaging agents, for example, in the macrophage. UV sensitivity tests on M intracellulare and M tuberculosis strains mutant in katG revealed that the katG gene product does not play a demonstrable role in the survival of repair-competent mycobacterial cells after exposure to UV irradiation. The second aim of this study was to examine the regulation of expression of the M tuberculosis katG gene. An E. coli-mycobacterial shuttle vector, pJCluc, containing the luciferase reporter gene, was constructed and used to examine the katG promoter sequences. The region required for optimal expression in M. smegmatis was localized to a 559 hp fragment immediately upstream of the gene. Two transcription start sites were mapped and putative -10 and -35 promoter sequences identified. It was demonstrated that expression from the promoter peaks during late exponential phase, and declines during stationary phase, and that the promoter is induced by ascorbic acid, and is repressed by oxygen limitation and growth at elevated temperatures. An upstream element that increased expression from the M. tuberculosis katG and the M. paratuberculosis PAN promoters was identified, and shown to bind to one or more M smegma/is proteins. Similar results were obtained in M bovis BCG. Understanding the regulation of gene expression in mycobacteria is essential for determining the processes that govern interaction with the host. This study provides information on both the mycobacterial transcription signals and gene regulatory mechanisms.